Brand Experience and Brand Love as Drivers of Brand Loyalty through Self-Determination in Online Gaming - Muhammad Dzakiy Al Fuadi; Endy Gunanto Marsasi (Jurnal Ecogen, 2026)
The rapid development of the digital gaming industry, particularly in the MOBA genre, has intensified competition and highlighted the importance of building long-term user loyalty. This study aims to analyze the influence of brand experience, engagement interaction, and impression on brand trust, brand love, and brand loyalty among Generation Z. The research employs a quantitative approach with an explanatory design through a survey of 150 respondents, analyzed using Structural Equation Modeling (SEM). The findings indicate that engagement interaction and impression have a significant effect on brand trust, while brand trust strongly influences brand love, which in turn drives brand loyalty. Although brand experience contributes to emotional attachment, this variable does not have a direct effect on trust. The study concludes that loyalty in the digital gaming industry is shaped by psychological and relational factors, particularly trust and emotional attachment, rather than solely by functional experience.